A review of the mealybugs (Hemiptera: Coccoidea: Pseudococcidae, Putoidae and Rhizoecidae) of Iran, with descriptions of four new species and three new records for the Iranian fauna - Moghaddam, Masumeh (Zootaxa, 2013)
Fifty-one species in 27 genera of Pseudococcidae, plus one species of Rhizoecidae and one species of Putoidae have been recorded from Iranbased on literature data and on the material in the collection of the Hayk Mirzayans Insect Museum, Iran. Keys to the Iranian genera and species based on adult female morphology are provided and the distribution data of each species and their host-plants are given. Adult females of each species are illustrated in detail. The species Paracoccus burnerae (Brain), Phenacoccus pumilus (Kiritshenko) and Ph. hordei (Lindeman) are recorded for the first time in Iran. Four new species, Exallomochlus balouchestanensis Moghaddam sp. n., Peliococcus ilamicus Moghaddam sp. n., Phenacoccus karkasicus Moghaddam sp. n. and Phenacoccus iranica Moghaddam sp. n. are described.